A quadratic polynomial, whose zeroes are -3 and 4, is (A) x2 - x + 12 (B) x2 + x + 12 (C) (x2/2)-(x/2)-6 (D) 2x2 + 2x -24

Solution

(C) (x2/2)-(x/2)-6

option (C) is the correct answer.

Explanation:

Sum of zeroes,

α+ β= -3+4 =1

Product of Zeroes,

αβ = -3× 4 = -12

Therefore, the quadratic polynomial can be expressed as,

x²- (sum of zeroes)x+(product of zeroes)

= x²- (α+ β)x+(αβ)

= x² – (1)x + (-12)

= x² – x -12

On dividing by 2, we get

= x²/2 – x/2 -12/2

= x²/2 – x/2 -6

Was this answer helpful?

 
   

4.5 (1)

(1)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question